New DTC strategy of multi-machines single-inverter systems for electric vehicle traction applications - Taibi Ahmed; Hartani Kada; Allali Ahmed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In high power traction system applications two or more machines are fed by one converter. This topology results in a light, more compact and less costly system. These systems are called multi-machines single-converter systems. The problems posed by different electrical and mechanical couplings in these systems (MMS) affect various stages of the systems and require control strategy to reduce adverse effects. Control of multi-machines single-converter systems is the subject of this paper. The studied MMS is an electric vehicle with four in-wheel PMS motors. A three-leg inverter supplies two permanent magnet synchronous machines which are connected to the front right and rear right wheels, and another inverter supplies the left side. Several methods have been proposed for the control of multi-machines single-inverter systems, the master-slave control structure seems best adapted for our traction system. In this paper, a new control structure based on DTC method is used for the control of bi-machine traction system of an EV. This new control has been implanted in simulation to analyze its robustness in the presence of the various load cases involved in our electric vehicle traction chain. Simulation results indicated that this structure control allowed the stability of the traction system.